Modified reporting of positive urine cultures to reduce treatment of asymptomatic bacteriuria in long-term care facilities: a randomized controlled trial. Issue 5 (14th October 2022) - Rehan, Zahra; Pratt, Claire; Babb, Kim; Filier, Brenda; Gilbert, Laura; Wilson, Robert; Daley, Peter
Abstract: Objectives: We conducted a prospective, randomized, unblinded superiority trial of the safety and efficacy of modified reporting of positive urine cultures to improve the appropriateness of treatment for asymptomatic bacteriuria (ASB) and urinary tract infection (UTI) in long-term care facilities (LTCFs). Methods: Consecutive positive urine cultures collected from LTCF patients were randomized between standard (identification and susceptibility) or modified (without identification and susceptibility) laboratory reports. Exclusion criteria were current antibiotic treatment, neutropenia, or transfer to acute care. The diagnosis of UTI or ASB was made prospectively. Results: One hundred and sixty-nine urine cultures were considered, 100 were randomized and included in ITT analysis, and 96 were included in PP analysis. Sixty-two out of 100 (62%) patients had ASB [41/62 (66%) treated] and 38/100 (38%) had UTI [35/38 (92%) treated]. The lab was called to report the identification and susceptibility in 31/51 (61%) modified reports. The rate of appropriate treatment was higher in the modified report arm: 31/51 (61%) versus 25/49 (51%) (+10%, P  = 0.33). Untreated ASB was higher in the modified report arm: 13/32 (41%) versus 8/30 (27%) (+14%, P  = 0.25). There were two deaths (one treated ASB, one untreated ASB) and 15 adverse events in the modified arm. There were no deaths ( P  = 0.16) and 11 adverse events ( P  = 0.43) in the standard arm. Three patients with untreated UTI survived. Conclusions: Modified reporting of urine culture improved the appropriateness of treatment by reducing treatment of ASB, but not significantly. Many LTCF prescribers requested standard urine culture reports. Modified reporting may not be suitable for LTCF implementation.